The everyday of people waiting for kidney transplantation - Micheli Rezende Ferreira Cruz; Anna Maria de Oliveira Salimena; Ivis Emília de Oliveira Souza; Maria Carmen Simões Cardoso de Melo (Universidade Federal do Ceará, 2016)
Objective: to understand the everyday of people experiencing the waiting list for kidney transplantation. Methods: this is a qualitative research, based on Heideggerian phenomenology. 14 deponents participated in hemodialysis and registered on the waiting list for kidney transplantation. Phenomenological interview with the research question: How is the experience awaiting the kidney transplant? Color marking technique for analyzing demarcating lines that show similarity, of these, emerged the essential structures that enabled the units of meaning. Results: changing lifestyles, imposing a routine and rigidity of treatment signaling everyday stress and exhaustion of hemodialysis being. Emerging from the modes of gossip, curiosity, and bureaucracy, unfolding-inauthentic and impersonal regarding their care. Conclusion: hemodialysis dependence and awaiting kidney transplantation transfer care for family/professional caregivers. To understand the everyday marked by impositions and restrictions, the reflection about how professional health interaction/being-care becomes important.